Indicators of Prescription Drugs and Oral Dietary Supplements among Inhabitants of Nursing Homes - Mohammed Salman Almazeedi,; Ahmed Saud Alghanim,; Mossa Ali Alsaad,; Ayat Jaber Alhamadah,; Shaker Abdullah Alabdullah,; Adnan Ahmed Bu-Hassan,; Yousef Yassen Alhashim,; Hayder Taher Alhumaid,; Haya Saad Mubarak Alqahtani,; Atif Nasser Alatafi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Malnutrition is a common issue among elderly individuals, especially in nursing homes, leading to various health complications such as disability, falls, and hospitalizations. Oral nutritional supplements (ONS) are frequently used to address malnutrition in this population, but factors influencing their prescription remain poorly understood. This study aimed to identify both resident-specific and nursing home-specific factors associated with ONS prescription in nursing home residents. Methods: A study was performed to examine resident characteristics (e.g., age, disability, comorbidities, malnutrition indicators) and nursing home characteristics (e.g., ownership, GP staffing, presence of dietitians, meal preparation) in relation to ONS prescription. Multivariate binary logistic regression was used to assess the association between these variables and the likelihood of receiving ONS. Results: Of the participants, 7.8% were prescribed ONS. Factors associated with increased ONS prescription included advanced age, low BMI (<21 kg/m²), recent weight loss, greater disability in activities of daily living, pressure sores, pain, and a higher number of hospitalizations. Nursing homes with specialized geriatric training for coordinating physicians, dietitians on staff, and provision of evening snacks were more likely to prescribe ONS. On-site meal preparation, fasting duration, and the number of medications were associated with reduced likelihood of ONS prescription. Conclusion: Both resident-related and nursing home-related factors influence the prescription of ONS in nursing homes. Specifically, advanced age, low BMI, and greater disability are key predictors for ONS use, while nursing home infrastructure, including the presence of dietitians and specialized training for healthcare providers, also plays a significant role. Addressing these factors may enhance ONS prescription practices and improve nutritional care for nursing home residents.